Implementation of Enhanced Recovery After Surgery (ERAS) Protocols in Abdominal Surgery - Anisah Nazrah Siregar; Anna Millizia (Pusat riset dan Inovasi Nasional, 2025)
Enhanced Recovery After Surgery (ERAS) is a multidisciplinary, evidence-based perioperative care approach designed to minimize the stress response to surgery, preserve organ function, and improve clinical outcomes. A substantial body of evidence has demonstrated that implementing ERAS protocols in elective procedures not only accelerates patient recovery but also reduces healthcare costs. Surgery, one of the most commonly performed medical interventions worldwide particularly major procedures such as abdominal and colorectal surgery carries a high risk of postoperative complications. These complications contribute to increased morbidity, mortality, and economic burden for both patients and healthcare systems. This situation presents a particular challenge in the era of universal health coverage, which demands efficiency in terms of time, cost, and resource utilization. ERAS implementation has been proven to enhance postoperative recovery, shorten hospital stays, and expedite the return of normal physiological function compared to conventional surgical care, especially in lower abdominal surgeries and colorectal resections. A literature review was conducted by searching relevant articles through Google Scholar using inclusion criteria such as publications from 2018 onwards, focused on ERAS in abdominal surgery, full-text availability, and academic journal sources. The data were analyzed using a matrix table comparing research methods, study populations, research locations, and reported outcomes. ERAS protocols have shown to be effective in abdominal surgical procedures for improving patient recovery and reducing postoperative complications.